Analysis Thematic Progression Pattern in Sangkuriang Folklore - Devi Agung Ratna Dewi (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2026)
This research is aimed to find out the pattern of thematic progression. The data for this study is derived from Sangkuriang folklore. There were three types of thematic progression found in the text “Sangkuriang” folklore story. They were theme reiteration, the zig-zag pattern and the multiple – rheme pattern. This research was conducted using qualitative support and simple quantitative count for accurance of each types. Theme reiteration is one basic way to keep a text focused to simply reiterate element. As we saw with lexical cohesion, repetition is an effective means of creating cohesion. The Zig-Zag pattern, an element which is introduced in the Rheme in clause gets promoted to become the Theme of clause. This multiple –Rheme pattern is also common in longer expository texts. The multiple – Rheme pattern provides the underlying organizing principle for a text, with both the zig-zag and theme reiteration strategies being used for elaborating on each of the main thematic points.